2022
DOI: 10.3389/feart.2022.849501
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Interaction Between Deforestation and Rice Cultivation During the Holocene in the Lower Yangtze River, China

Abstract: Human activity has transformed the Earth’s landscapes pervasively for thousands of years, and the most important anthropogenic alteration was the clearing of forests and the establishment of agriculture. As a center of rice domestication and early population growth, the lower Yangtze River has been extensively transformed in the Holocene. However, the timing, extent, and process of deforestation and its relationship with the intensification of rice cultivation remain controversial. Here, four representative ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 58 publications
0
11
1
Order By: Relevance
“…2022a; He et al . 2022), with active fire events mainly in the mid‐Holocene, differing from the fire records from natural sediments mentioned above and from this study (Fig. 3).…”
Section: Discussioncontrasting
confidence: 85%
See 2 more Smart Citations
“…2022a; He et al . 2022), with active fire events mainly in the mid‐Holocene, differing from the fire records from natural sediments mentioned above and from this study (Fig. 3).…”
Section: Discussioncontrasting
confidence: 85%
“…At the same time, other studies in the region showed different trends. Sediment profiles located in or very close to archaeological sites (<100 m) show frequent fire activity synchronizing with high intensity of human activity (Zong et al 2007;Innes et al 2009;Liu et al 2020;Li et al 2021;Dai et al 2022a;He et al 2022), with active fire events mainly in the mid-Holocene, differing from the fire records from natural sediments mentioned above and from this study (Fig. 3).…”
Section: Impact Of Human Activity On Fire Eventsmentioning
confidence: 45%
See 1 more Smart Citation
“…At the meantime, macrofossil remains and microfossil evidence from the JTS site would indicate rice cultivation was performed by the local people throughout their occupation period ( ca. 8,300–7,800 cal yr. BP) at the site ( Zhejiang Provincial Institute of Cultural Relics and Archaeology, Ningbo Institute of Cultural Heritage Management, Yuyao Hemudu Site Museum, 2021 ; He et al, 2022 ). Moreover, archaeological findings from the JTS site suggested an upgrade of farming tools from shell and bone Si (耜) ploughs to wooden ploughs to facilitate rice cultivation ( Zhejiang Provincial Institute of Cultural Relics and Archaeology, Ningbo Institute of Cultural Heritage Management, Yuyao Hemudu Site Museum, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Diatom and pollen evidence indicated a freshwater environment at the Kuahuqiao site ( Zong et al, 2007 ; Wu et al, 2016 ) and a brackish wetland setting in the YJV provided material bases for human settlements ( Supplementary Table S1 ). Charcoal analysis from both sites indicated that local people had adopted a slash-and-burn strategy to open vegetation for more resources and arable land ( Hu et al, 2020 ; He et al, 2022 ). Rice cultivation was confirmed at both sites assisted by primitive farming tools ( Figure 8A ).…”
Section: Discussionmentioning
confidence: 99%